Creating a logo a process for designer - Vallis, Adrian; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2004)
Using the VEA logo as a real life example, the process of conceptualising, designing and producing a logo is examined. Designers give their insight into developing a logo. Taken from the client arriving at the office with a design brief, through research and the creative processes leading to the presentation of a first draft and concluding with the production and launch of the logo
Title from title screen
Sound, Wayne Martin ; camera, Adrian Vallis ; editor, Jared Marshall
Interviewees: Glenn Harvey, Sean Pethick, Kieran Doolan
DVD format
Keywords: Logos (Symbols) -- Design; Trademarks -- Design